Pemetaan User Journey untuk Sistem Informasi Praktik Kerja Lapangan Fakultas Ilmu Komputer Universitas Brawijaya - Annisa Nurfitri; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Faculty of Computer Science (Filkom) Universitas Brawijaya is one of the educational institutions that already has a web-based information systems that can be used to record, process and provide informations to facilitate the deployment of information related to teaching and learning activities up to academic services. However, there are several formerly documents of academic activities that are still documented manually, one of them is Field Work Practice activities. Based on the interview with the students, it was found that the activites of Field Work Practice that has not been computerized well caused its process become ineffective and inefficient, which also affected the user experience. This study uses the User Journey Mapping method that can dig deeper the problems based on the user experience and provide the ideas of solutions towards the problems. The stages that carried out in this study are identification of the actors, identification of the activities then mapping it to the User Journey Retrospective, mapping the thoughts, emotions, and ideas of solutions, and then checking the User Journey Retrospective map, and finally mapping the Prospective User Journey based on the ideas of solution which obtained by the User Journey Retrospective map. Mapping of User Journey Prospective is done by creating a scenario of the Field Work Practice which integrated with the Filkom Apps information systems. The final results of the study indicate that the User Journey Prospective map is accordance with the idea of ​​solution given towards the problems that are available on the User Journey Retrospective map.